Use of English in the School of Business at the University of Iceland. Effects of English Language Usage on Quality of Education - Dagný Lára Guðmundsdóttir 1990- (2013)
This study examines views on how the English curriculum affects students’ learning and quality of education. It begins with a review of the literature on the spread of English and its use as a lingua franca in the world. It then continues and discusses the status of English in Iceland and in academia and then explores the market of English textbooks and their usage at universities, with particular reference to the use of English in the School of Business at the University of Iceland. Almost the entire curriculum in Iceland at a university level is in English but previous studies have shown that a considerable part of the students at the University of Iceland have in difficulties reading English curriculum. This study focuses on students in the School of Business for whom English skills are important for their future career but over 90% of their curriculum is written in English while the language of instruction is Icelandic. This has been termed as simultaneous parallel code as students must negotiate between two languages to access the curriculum. The results of the study imply that although students believe they are prepared to tackle the curriculum in English and believe studying in English has advantages, they also perceive that working in two linguistic codes increases workload and poses constraints.